Gangguan Berbicara pada Penderita Gagap (Studi Kasus Pada Subjek HA) - Fauzia, Ami; Ihsan, Rodiyal (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Speaking disorders are aspects of language related to the ability to articulate language in the form of a series of sounds that form a meaning that can be understood by the interlocutor, the most common speaking fluency disorder is stuttering. The case study on Subjek HA aims to find out and explain the form of stuttering disorder, the index of fluency and the faktors that cause stuttering and the effect of stuttering on the fluency of speech of stutterers. This research is a case study that uses a descriptive approach. By using the listening method and the speaking method. The methods used in analyzing the data are speech sampling and speech analyzer, The results of this study show that there are several indications of stuttering, namely repetition, display, speech intensity, and silence in the subject's speech. The inexperience shows that the results of stuttering affect the fluency of speech. It can also be seen from the subject's speech rate of 90 words/minute which is quite low compared to the normal speech rate of 160 words/minute. The acquired faktor (acquired stuttering) is a faktor that causes stuttering disorders in speakers.